A COMPARATIVE STUDY OF AGGRESSION AMONG MALE AND FEMALE OF SENIOR SECONDARY SCHOOL STUDENTS - Dr.Meena, Mrs.Priya Mittal, Mrs.Suman, Dr.Ganga (EPRA International Journal of Environmental Economics, Commerce and Educational Management (ECEM), 2023)
The main aim of this study was to examine the aggression among senior secondary school students in relation to different dimensions of aggression. For this, 100 male and 100 female senior secondary school students from different Govt. schools of Sonipat Distt. Of Haryana were included in the present study. Selected students were tested with Arnold H.Buss and Mark Perry scale (1999) on aggression. Obtained data were analysed by applying descriptive statistics (Mean, S.D.) and t-ratio. Result revealed that females are high on Physical aggression but males students are higher on Verbal aggression. Similarly, female students are having more anger than males but male students having more hostility than female students. The present findings have important implication for teachers to understand the behavior of students.